ANALISIS KOMPETENSI KEWIRAUSAHAAN KEPALA PAUD SEKECAMATAN TAMPAN KOTA PEKANBARU - Syarifah Nurzila Rapika; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to: 1. To know the competence of entrepreneurship by Early Childhood Education headmaster at Tampan sub district, Pekanbaru City. 2. To know the innovations made by Early Childhood Education headmaster at Tampan sub district, Pekanbaru City. 3.To find out the hard work done by Early Childhood Education headmaster at Tampan sub district, Pekanbaru City. 4.To know the motivation of the headmaster of Early Childhood Education at Tampan sub district, Pekanbaru City. 5.To know the unyielding attitude that has the headmaster of Early Childhood Education at Tampan sub district, Pekanbaru City. 6.To know the attitude of entrepreneurial instinct that is owned by Early Childhood Education headmaster at Tampan sub district, Pekanbaru City. 7.To find out the creative attitude of the headmaster of Early Childhood Education at Tampan sub district, Pekanbaru City. 8.To know the skill of utilizing partnership network owned by Early Childhood Education headmaster at Tampan sub district, Pekanbaru City. This research type is descriptive research that is research conducted to independent variable , that is without making comparison, or linking with other variable. The sample of this research is Early Childhood Education headmaster at Tampan sub district, Pekanbaru City consisting of 48 people. Data collection using questionnaires. Based on the results of the research note that the Head of Early Childhood Education at Tampan sub district, Pekanbaru City has an average of 79 , 54 % with good category.Keywords : Entrepreneurship Competence